Ocular Manifestation and Visual Outcome of Zika Virus Infection Associated with Congenital Zika Syndrome - Anak Agung Dewi Adnya Swari; Ida Ayu Ary Pramita; I Gusti Ayu Made Juliari; I Made Ady Wirawan (International Journal of Biomedical Science and Travel Medicine, 2024)
Introduction: Zika virus disease is an acute infectious disease caused by Zika virus transmitted through Aedes mosquitoes. The ocular findings in children with zika virus, cause a broad spectrum of ocular manifestations and present up to 55% of affected infants. This review explores its ocular manifestations and visual acuity of zika virus infection. Methods: A systematic review was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) from the PubMed databases. Assessment of study quality and risk of bias were assessed by using checklist from Joanna Briggs Institute (JBI). Results: We included 9 literatures with most literatures came from Brazil. Zika virus result in various ocular manifestations, ranging to congenital glaucoma, microphthalmia, congenital cataract, lens subluxation, iris coloboma, and retinopathy. The ocular manifestations of zika virus significant impact on visual outcome. Conclusion: Children with zika virus infection present of ophthalmological abnormalities and high risk for severe visual impairment.